If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(1/2)*y-((1/3)*x)-1 = 0
(-1/3)*x+(1/2)*y-1 = 0
1/2*y-1/3*x-1 = 0 // - 1/2*y-1
-1/3*x = -(1/2*y-1) // : -1/3
x = (-(1/2*y-1))/(-1/3)
x = -3*(1-(1/2*y))
x = -3*(1-(1/2*y))
| -3=3p+11-2p | | 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p | | -9=-6p-7+7p | | y-4=(x-7)(x-7) | | 3=-4.5+4y | | -9=5p-12-4p | | x+19=139 | | 22x=-12 | | 2=-4.5+4y | | -16=-5(8n+3) | | -6=-9p+14+10p | | 1=-4.5+4y | | 121b^2-100= | | 0=-4.5+4y | | 2x-19=1421 | | 27=6+8+c | | 10x+20/25x+20 | | 191=-3x+7(4x-12) | | -6=-5p-12+6p | | 2z-6-7=-30 | | -28n^2=-96-184n | | -176=7x+5(-3x-16) | | 4x+14=2894 | | -5x+2(-4x+6)=77 | | 8(x+6)-8=40 | | -22=-4 | | 28-8x=x |